Blueberry juice protects osteocytes and bone precursor cells against oxidative stress partly through SIRT1. Issue 6 (20th April 2019) - Domazetovic, Vladana; Marcucci, Gemma; Pierucci, Federica; Bruno, Gennaro; Di Cesare Mannelli, Lorenzo; Ghelardini, Carla; Brandi, Maria Luisa; Iantomasi, Teresa; Meacci, Elisabetta; Vincenzini, Maria Teresa
Abstract : Oxidative stress and abnormal osteocyte apoptosis are often related to dysregulation of bone turnover and chronic bone loss, and so fruit and vegetables with high antioxidant potential may play an important role in the prevention and/or management of osteoporosis. Osteocytes are the main regulators of bone remodelling. For the first time, we demonstrate here that blueberry juice (BJ), obtained from Vaccinium myrtillus, rich in polyphenols, shows antioxidant and antiosteoclastogenic properties in MLO‐Y4 osteocytes. We report that BJ prevents oxidative stress‐induced apoptosis and reverses the increase in receptor activator of nuclear factor κB ligand and sclerostin expression, crucial factors for osteoclast activation and bone resorption. BJ is also able to prevent oxidative stress‐induced cell cytotoxicity in bone marrow mesenchymal stromal cells (MSCs), which are considered to be an important tool for cell therapy in bone disorders. No significant difference in preventing these events was observed between BJ and blueberry dry extract containing equal amounts of total soluble polyphenols. We have also shown that blueberry acts as both an antioxidant and an activator of sirtuin type 1, a class III histone deacetylase involved in cell death regulation and considered a molecular target for blocking bone resorption without affecting osteoclast survival. Overall, these novel data obtained in osteocytes and MSCs may help us clarify the mechanisms by which blueberry counteracts oxidative stress‐induced damage in bone remodelling and osteogenesis at the cellular and molecular level. Our findings are consistent with the reported beneficial effects of blueberry on bone tissue reported in animal studies, which suggest that blueberry may be a useful supplement for the prevention and/or management of osteoporosis and osteogenic process. Abstract : Blueberry juice (BJ), which is rich in polyphenols, shows antioxidant and anti‐osteoclastogenic properties in MLO‐Y4 osteocytes, which are the main regulators of bone remodelling. It also prevents oxidative stress‐induced cell cytotoxicity in bone marrow mesenchymal stromal cells (MSCs), which are important for osteogenesis. BJ acts both as an antioxidant and as an activator of sirtuin 1, which is considered a molecular target for blocking bone resorption without affecting osteoclast survival.